Mechanical property testing of 3D printed structures - Chee, Shu Ping (Nanyang Technological University, 2022)
This Final Year Project (FYP) is about testing of mechanical properties of 3D printed structures of different geometries and dimensions. Three-point bending test will be conducted on the structures and Stress-Strain curve will be plotted to analyse the behaviour. The literature review provides the required information for conducting the investigation, including a basic introduction of the different arrangement of square structures that are currently used and the different method of production available in the laboratory. Moreover, square geometries in the chainmail were easier for fabrication in terms of Design for Manufacturability (DFM) and it is easier to achieve different interweaving technique. In this study, a combination of granular, layer and fibre jamming which concluded to be chainmail jamming was explored with 6 different samples printed with 3D Form Labs Desktop printer, mainly 4 sample with identical spacing effect but different ring width – 4.05mm, 4.35mm, 4.65mm and 4.95mm, and 2 other sample of different spacing effect as the first but with same ring width of 4.95mm. The chainmail underwent a three-point bending test with Mark-10 Universal testing machine. Each chainmail specimen undergoes 5 runs of three-point bending test and the datasets will be analysed using software such as Python and graph will be plotted against each other to compare the trends of the Stress and Strain. With the graph plotted, analysis will be done, and comparison will be made.